SEA-AIR INTERACTION ON RAINFALL STUDY USING COUPLED MODELING SCENARIO (CASE STUDY NORTH MOLUCCA) - OKTIVIA (NIM 22405002), RESSY
The maritime continent, Indonesia has various distinct local climate, whereas one of them has a strong local climate over Molucca. Observation data show that the local monthly rainfall distribution has a maximum value in the middle of the year, and known as anti-monsoonal pattern. But there are yet not many researchers to investigate that pattern. This study employs the global ocean model from Max Planck Institute-Ocean Model and the atmospheric model from Max Planck Institute-Regional Climate Model or Regional Atmospheric Model. Both models are coupled using an OASIS coupler. The task of the coupler is to time synchronization for coupling processes or data exchange at every six hour (the coupled time step), because both models have been ran at different time steps. This study uses data from the European Centre for Medium-Range Weather Forecasts reanalysis, ERA15. Coupled model simulation has been ran using two different scenarios. For the first scenario, which is also used as the control run, the whole atmospheric model domain receives sea surface temperature (SST) from the ocean model. This means that there is sea-air interaction process (coupled on). While, for the second scenario, the masking method is applied (coupled off), or SST taken from ERA15 for Molucca region only. For the other domain, SST comes from ocean model. So, there is no sea-air interaction process in Molucca region. Simulation results of local SST variability indicate that the interannual rainfall distribution from coupled-on scenario better than that one. That local SST variability affects more on Molucca's local rainfall pattern. In this case, characteristic difference of rainfall type that influenced is more on convective type of rainfall. This result indicates that rainfall variability is influenced more strongly by local ocean climate, rather than large scale effect such as the regional wind circulation. Mean difference significance analysis coupled-off to coupled-on also shows that, interannual rainfall significance difference distribution is influenced more strongly by the interannual convective type of rainfall, whereas there is no significance difference on stratiform type of rainfall. During boreal spring period, differences of convective and stratiform types of rainfall and the interannual rainfall significance difference are much fluctuated rather than those during boreal summer period. Because during boreal spring period, there is an interaction between sea and air, especially between the latent heat and SST variables that influence each other.